Improving In-plant Logistics: A Case Study of a Washing Machine Manufacturing Facility - Ucar, Cagdas; Bayrak, Tuncay (UNIV CINCINNATI INDUSTRIAL ENGINEERING, 2015)
This study presents a case study on the enhancement of in-plant logistics at a discrete manufacturing plant using lean manufacturing/logistics principles. Two independent application scenarios are presented. In the first application, we improve the operation of a supermarket (small internal warehouse) from the ergonomics point of view by (1) placing heavy boxes on waist-level shelves, and (2) applying rolling racks/trolleys to release the physical load on the workers. In the second application, the logistic processes related to a new supermarket are fundamentally re-designed.
Keywords: In-plant logistics; supermarket; milkrun; ergonomics; fatigue; just-in-time production; RISK-FACTORS; Engineering